Assessment of Global and Local Alterations in Retinal Layer Thickness in Ins2 (Akita) Diabetic Mice by Spectral Domain Optical Coherence Tomography - Andrew W. Francis; Justin Wanek; Mahnaz Shahidi (Journal of Ophthalmology)
Purpose/Aim. The Ins2 (Akita) mouse is a spontaneous diabetic mouse model with a heterozygous mutation in the insulin 2 gene that results in sustained hyperglycemia. The purpose of the study was to assess global and local retinal layer thickness alterations in Akita mice by analysis of spectral domain optical coherence tomography (SD-OCT) images. Materials and Methods. SD-OCT imaging was performed in Akita and wild-type mice at 12 and 24 weeks of age. Inner retinal thickness (IRT), outer retinal thickness (ORT), total retinal thickness (TRT), and photoreceptor outer segment length (OSL) were measured. Mean global thickness values were compared between Akita and wild-type mice. Local thickness variations in Akita mice were assessed based on normative values in wild-type mice. Results. Akita mice had higher blood glucose levels and lower body weights (p<0.001). On average, IRT, ORT, and TRT were approximately 2% lower in Akita mice than in wild-type mice (p≤0.02). In Akita mice, the percent difference between retinal areas with thickness below and above normative values for IRT, ORT, and TRT was 22%, 32%, and 38%, respectively. Conclusions. These findings support the use of the Akita mouse model to study the retinal neurodegenerative effects of hyperglycemia.